2021
DOI: 10.1108/ijopm-09-2020-0662
|View full text |Cite
|
Sign up to set email alerts
|

Embracing supply base complexity: the contingency role of strategic purchasing

Abstract: PurposeThis paper aims to empirically examine the moderating role of strategic purchasing on the relationship between supply base complexity (SBC) and purchasing performance.Design/methodology/approachSurvey data were collected from 209 firms listed in the Capital Top 500 Firms of Turkey. Measurement properties were assessed via confirmatory factor analysis, and the conceptual model was tested via hierarchical regression analysis. A supplementary analysis based on 14 semi-structured interviews was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 60 publications
(250 reference statements)
1
50
0
Order By: Relevance
“…multiple sourcing—necessary to deal with exported complexity to the SC in the form of flexibility and innovation requirements (Aitken et al. , 2016; Ateş and Memiş, 2021; Sharma et al. , 2020; Wiengarten et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…multiple sourcing—necessary to deal with exported complexity to the SC in the form of flexibility and innovation requirements (Aitken et al. , 2016; Ateş and Memiş, 2021; Sharma et al. , 2020; Wiengarten et al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies reported negative impacts of increasing SC complexity on performance and product quality (e.g. Ateş and Memiş , 2021; Bozarth et al. , 2009; Chand et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2.1 Theoretical background Industry in general, and the manufacturing industry in particular, are currently immersed in a significant technological transformation that involves every organization with major effects along the entire SC (Ghobakhloo, 2020). In recent years, SCs have become more complex for several reasons, including the uncertainty that surrounds them and the behavior of the stakeholders in the SC (Ates ¸and Memis ¸, 2021;Serdarasan, 2013).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%